Optimizing Technical Entrepreneurship: Instrument Development for Assessing Technopreneurial Behavior Among Vocational High School Fashion Design Students - Imami Rahayu; Ekohariadi Ekohariadi; Ratna Suhartini (IJORER : International Journal of Recent Educational Research, 2024)
Objective: Technopreneur behavior refers to the traits, attitudes, and actions of an individual or group involved in technology-based entrepreneurship. Technopreneur is a combination of the word’s "technology" and "entrepreneurship," and encompasses the application of technology and innovation in a business context. The purpose of this study is to develop an instrument that can measure the technopreneur behavior of Vocational High School Fashion School students. Method: This research is a development research with a 4D model, namely Define, Design, Development, and Development. Instrument was tested on 30 students of Vocational High School 3 Kediri. Results: The results of the study stated that based on the CVR, correlation-total, OMS, and IMS criteria, there were 2 items that did not meet so that these items had to be revised or discarded, while other items were declared to meet the criteria. And the results of the instrument trial stated that 3.33% of students had techopreneur behavior in the "high distinction" category, 83.3% in the "Distinction" category, and 13.3% in the "Credit" category. Novelty: This research presents novelty by designing a unique instrument that focuses on the technopreneur behavior of VHS Tata Busana students. This innovative approach includes the integration of technological and entrepreneurial aspects, active stakeholder participation, the application of revolutionary learning models, and adaptation to the latest technological developments.